.Enhancing The 21st Century Life Skills Of University Students Using Whole Brain Literacy, Experiential Learning Theory, And Appreciative Inquiry: An Action Research For Assumption University - Israngkul na Ayudthaya, Puntharee; Chavez, Gloria S.; Seelaungsawat, Lertchanta (Scholar: Human Sciences, 2019)
This research investigated the effect of organization development interventions (ODI) using three modalities namely: Whole Brain Literacy (WBL), Experiential Learning Theory, and Appreciative Inquiry (AI) in enhancing the 21st Century Life Skills of undergraduate students in Assumption University of Thailand. An action research was conducted in three phases; pre-ODI, ODI, and post-ODI where both quantitative and qualitative research methods were used to explore, assess and gather the data to enhance the life skills of students which included thinking skills, action-related skills, creativity skills, relationship skills, and self-management skills. The quantitative data were collected by using the same set of questionnaire which has been developed from relevant sources on life skills development during before and after OD interventions to measure life skills with close-ended questions while the qualitative data were collected from an interview, observation, and group discussion. The Design of the Action Research used two groups of 30 students each, the first group went through Organization Development Interventions (ODI) and the second group of 30 was the control group without the ODI. The participants were selected by using Purposive sampling technique. The quantitative data was analyzed by using Paired Sample T-Test and the content analysis was used for the qualitative data. The findings reveal that OD interventions helped enhance the confidence level of life skills of the students involved in the study. As a recommendation, a new model for enhancing the life skills of students called “Life Skills Enhancement Model for Students: the Processes of Learning and Living on Purpose was developed.